(adsbygoogle = window.adsbygoogle || []).push({}); Edit:I originally wrote that ##\mathcal A## is a Banach algebra. The assumption that goes into the theorem is stronger. It's a C*-algebra. I am however still mainly interested in the claim that ##\mathcal A_1##, as defined below, is a Banach sub-algebra of ##\mathcal B(\mathcal A)##.

Let ##\mathcal A## be a C*-algebra without identity. For each ##x\in\mathcal A##, define ##L_x:\mathcal A\to A## by ##L_xy=xy## for all ##y\in\mathcal A##. It's trivial to show that ##L_x\in\mathcal B(\mathcal A)## for all ##x\in\mathcal A##. The map ##x\mapsto L_x## with domain ##\mathcal A## will be denoted by L. It's easy to show that L is an isometric algebra homomorphism into ##\mathcal B(\mathcal A)##. Define ##\mathcal A_1=\{L_x+\lambda|x\in\mathcal A,\, \lambda\in\mathbb C\}##. The notation ##\mathcal A_1=L(\mathcal A)+\mathbb C## makes this definition easier to remember. ##\mathcal A_1## is closed under addition, scalar multiplication and multiplication. Supposedly* (this is what I want to prove), it's also complete. Since it's a subset of ##\mathcal B(\mathcal A)##, every Cauchy sequence is convergent. It's just not obvious that the limit of a convergent sequence in ##\mathcal A_1## is in ##\mathcal A_1##. So I want to prove that it is.

*) The claim is made by Conway in "A course in operator theory", in the proof of theorem 1.5, on page 3. http://books.google.com/books?id=gt...way operator&hl=sv&pg=PA3#v=onepage&q&f=false. His notation is slightly different from mine. (In particular, he writes λ where I write L)

Some of my thoughts: Let ##(T_n)_{n=1}^\infty## be an arbitrary convergent sequence in ##\mathcal A_1##. Let ##(x_n)## and ##(\lambda_n)## be sequences in ##\mathcal A## and ##\mathbb C## respectively, such that ##T_n=L_{x_n}+\lambda_n##. It would be nice if we could use that ##(T_n)## is Cauchy, to show that these two are Cauchy, and therefore convergent. Then we can define ##x=\lim_nx_n## and ##\lambda=\lim_n\lambda_n##, and perhaps show that ##L_{x_n}+\lambda_n\to L_x+\lambda##. But I don't see a way to proceed from

$$\varepsilon>\|T_n-T_m\|=\|(L_{x_n}+\lambda_n)-(L_{x_m}+\lambda_m)\| =\|L_{x_n-x_m}+(\lambda_n-\lambda_m)\|.$$ When we're dealing with Hilbert spaces, the usual way to continue a calculation like this would be to square both sides of the inequality and then use the pythagorean theorem (assuming that the terms are orthogonal), but I don't see what to do here.

It looks like (I haven't worked through that part of the proof yet) that we can prove that the C*-identity holds, without proving completeness first, when the involution is defined by ##(L_x+\lambda)^* =L_{x^*}+\bar\lambda##. I was thinking that maybe we can use that somehow, but when I tried, it just made the calculation longer, and I ran into the same issue as above.

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Banach sub-algebra

**Physics Forums | Science Articles, Homework Help, Discussion**